Emotions of the ostomy patients due to colorectal cancer in the nursing care practice - Wiraszka, Grażyna (Polish Journal of Public Health, 2010)
Aim. The purpose of the research was the assessment of the emotions of patients with stoma resulting from the surgical treatment of colorectal cancer and the analysis of its social-demographic conditions. Material and the applied methods. A standardized FACT-C form (Functional Assessment of Cancer Therapy Scale – Colorectal) and the HADS (Hospital Anxiety and Depression Scale) were used. The research was carried out on 164 patients at the Świętokrzyskie Oncology Centre in Kielce. The control group was also used for the purpose of the research. Results. The emotional condition of the patients was really worse in comparison with the control group, considering the evaluation made in the EWB scale of the FACT-C questionnaire (p<0.05), as well with use of the HADS scale (for anxiety p<0.05; for depression p<0.01). Younger patients – those under 60 years old – (respectively p<0.001; p<0.01; p<0.01) with secondary or university education (p<0.05) and those who used the support from the self-supporting groups (p<0.001; for anxiety and depression p<0.05) achieved better results on the EWB scale, as well as on the scales measuring anxiety and depression. Moreover, the patients who were professionally active (p<0.05) achieved better results on the EWB scale and the patients who had support also felt less embarrassed because of the stoma (p<0.001). The results on the EWB and HADS scales really correlated with the results on the scales of biological and social functioning (rs= 0.63 to 0.85; rs= -0.66 to -0.89) and the scale of embarrassment with stoma (rs=0.74; rs=-0.75) and the scale of difficulty in caring the stoma (rs=0.69; rs= - 0.71 and -0.74). Conclusions. Emotions of the patients depend on the level of their biological and social performance, as well as on the level of coping with the stoma care; age, education, professional activity and support from self-supporting groups – are differentiating factors